Bioinspired Mesoporous Chiral Nematic Graphitic Carbon Nitride Photocatalysts modulated by Polarized Light. Issue 1 (14th December 2017) - Lin, Wensheng; Hong, Wei; Sun, Lu; Yu, Di; Yu, Dingshan; Chen, Xudong
Abstract: Endowing materials with chirality and exploring the responses of the material under circularly polarized light (CPL) can enable further insight into the physical and chemical properties of the semiconductors to be gained, thus expanding on optoelectronic applications. Herein a bioinspired mesoporous chiral nematic graphitic carbon nitride (g‐C3 N4 ) for efficient hydrogen evolution with polarized light modulation based on chiral nematic cellulose nanocrystal films prepared through silica templating is described. The mesoporous nematic chiral g‐C3 N4 exhibits an ultrahigh hydrogen evolution rate of 219.9 μmol h −1 (for 20 mg catalyst), corresponding to a high enhancement factor of 55 when compared to the bulk g‐C3 N4 under λ >420 nm irradiation. Furthermore, the chiral g‐C3 N4 material exhibits unique photocatalytic activity modulated by CPL within the absorption region. This CPL‐assisted photocatalytic regulation strategy holds great promise for a wide range of applications including optical devices, asymmetric photocatalysis, and chiral recognition/separation. Abstract : Black N white photographene : Bioinspired mesoporous g‐C3 N4 materials with supramolecular helical and liquid crystal layered structures were synthesized from chiral nematic CNC films through nanocasting with a SiO2 template. The g‐C3 N4 exhibited an ultrahigh hydrogen evolution rate that can be modulated by circularly polarized light during the photocatalytic processes.